Aviation titanium forge piece coating and treatment process thereof
By adopting a multi-layer coating system, combining the inner coating of TiO2, B4C, B2O3, MgO and other materials and the outer coating of B2O3, Al2O3, SiO2, KOH, TiB2 and other materials, the easy oxidation and combustion of titanium alloys at high temperatures is solved. The problem has significantly improved its antioxidant and flame retardant properties.
Patent Information
- Application Number
- CN202411974646.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Titanium alloys are prone to oxidation and combustion at medium temperatures or even high temperatures, resulting in limited application in the aerospace field. It is difficult for the prior art to effectively improve its oxidation and flame retardant properties.
A coating system consisting of an inner coating and an outer coating is composed of TiO2, B4C, B2O3, MgO, and the outer coating is composed of B2O3, Al2O3, SiO2, KOH, TiB2, and an intermediate coating is optionally added. For rare earth-modified re-granulated nanostructures Al2O3 and TiO2, an efficient antioxidant and flame retardant coating is formed through ball milling and spraying processes.
It significantly improves the oxidation and flame retardant properties of titanium alloy, extends its service life in high temperature environments, and enhances its application capabilities in higher temperature environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aerospace technology and relates to an aviation titanium forging coating. The invention also relates to a method for treating the aviation titanium forging by using the coating. Background Art
[0002] Aviation titanium forgings refer to titanium alloy forging products used in the aerospace field. They usually have the characteristics of high strength, low density, good corrosion resistance and weldability. Titanium alloys have been widely used in important load-bearing parts of aircraft and aircraft engines due to their excellent comprehensive performance. According to statistics, the weight ratio of titanium alloys used in foreign aircraft has reached about 30%. TC4 titanium alloy (Ti-6Al-4V) is one of the important materials, which is highly favored due to its lightweight advantages. Its density is about 4.43g / cm³, which is about 40% lower than that of heavy steel. The tensile strength of TC4 titanium alloy can reach 895-1050MPa, especially under high temperature conditions.
[0003] However, the oxide film formed on titanium alloy at medium or even high temperature is porous TiO 2 , it cannot effectively resist the inward diffusion of oxygen atoms. Therefore, there is a need for antioxidants for titanium alloys.
[0004] At the same time, since the ignition point of titanium alloy is lower than its melting point, high-speed moving titanium alloy parts may ignite the titanium alloy due to frictional heat and cause titanium fire accidents, which seriously endangers the safe use of aerospace vehicles. Therefore, there is also a need for flame retardancy for titanium alloy.
[0005] CN102675952B is an invention patent applied for by the applicant in 2012. The patented method can avoid the oxidation of titanium alloy to a certain extent, but there are still problems of oxidation and ineffective flame retardancy during long-term use.
[0006] However, titanium alloys are prone to oxidation and combustion at high temperatures, which limits their application in higher temperature environments. Therefore, it is particularly important to develop effective coating technology to improve its anti-oxidation and flame retardant properties. Summary of the invention
[0007] In order to improve the anti-oxidation and flame retardant properties of aviation titanium forgings, the purpose of the present application is to provide an aviation titanium forging coating and a treatment process thereof, which can effectively achieve the anti-oxidation and flame retardant effects on titanium alloys.
[0008] The present invention provides the following technical solution: an aviation titanium forging coating, comprising an inner coating and an outer coating, wherein the inner coating is composed of the following raw materials in terms of mass percentage: Inner coating: TiO 2 45%-50%, B 4C 6%-11%, B 2 O 3 28%-34%, MgO 6%-10%, the total mass percentage of the above raw materials is 100%; The outer coating layer is composed of the following raw materials in terms of mass percentage: Outer coating: B 2 O 3 0.7%-2.0%,Al 2 O 3 26%-36%, SiO 2 30%-32%, KOH 23.3%-30%, TiB 2 10-15%, the total mass percentage of the above raw materials is 100%.
[0009] Preferably, it also includes an intermediate coating, wherein the intermediate coating is a rare earth modified regranulated nanostructured Al 2 O 3 and TiO 2 .
[0010] Preferably, ZrO 2 and CeO 2 As a composite additive for synergistic modification, Al 2 O 3 、TiO 2 、ZrO 2 and CeO 2 The mass ratio is: 87:13:2:2.
[0011] Preferably, the inner coating layer is composed of the following raw materials in terms of mass percentage: TiO 2 45%, B 4 C 11%, B 2 O 3 34%, MgO 10%; The outer coating layer is composed of the following raw materials in terms of mass percentage: B 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%.
[0012] Preferably, the inner coating layer is composed of the following raw materials in terms of mass percentage: TiO 2 45%, B 4 C 11%, B 2 O 334%, MgO 10%; The intermediate coating is rare earth modified regranulated nanostructured Al 2 O 3 and TiO 2 , among which ZrO 2 and CeO 2 As a composite additive for synergistic modification, Al 2 O 3 、TiO 2 、ZrO 2 and CeO 2 The mass ratio is: 87:13:2:2; The outer coating layer is composed of the following raw materials in terms of mass percentage: B 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%.
[0013] Preferably, the coating treatment process comprises: cleaning the aviation titanium forging, drying; weighing TiO 2 45%, B 4 C 11%, B 2 O 3 34%, MgO 10%; then mix the raw materials and ball mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water and stir until the viscosity reaches 50-80 centipoise to prepare an inner coating paint, and then brush the inner coating paint on the surface of the aviation titanium forging with a thickness of 0.3mm and air dry naturally; then weigh B according to mass percentage 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%, then mix, and ball mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the inner coating with a thickness of 0.3mm, and dry naturally to complete the treatment of aviation titanium forgings.
[0014] Preferably, another treatment process of the coating includes: cleaning the aviation titanium forging, drying; weighing TiO 2 45%, B 4 C 11%, B 2 O 334%, MgO 10%; then mix the raw materials and ball mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water and stir until the viscosity reaches 50-80 centipoise to prepare an inner coating paint, and then brush the inner coating paint on the surface of the aviation titanium forging with a thickness of 0.3mm and dry it naturally; weigh Al according to the mass ratio of 87:13:2:2 2 O 3 、TiO 2 、ZrO 2 and CeO 2 , ball milling on a ball mill to form a powdery mixture, spray drying the ball milled powder to form a plasma sprayed powder form, heat treatment and plasma treatment of the spray dried powder, the particle size of which is 20 to 50 microns, and finally plasma spraying of the aviation titanium forgings after the inner coating is brushed, the spraying thickness is 0.3mm, and it is naturally air-dried to form an intermediate coating; then, according to the mass percentage, B 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%, then mix, and ball mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the intermediate coating with a thickness of 0.3mm, and dry naturally to complete the treatment of aviation titanium forgings.
[0015] The beneficial effects of the present invention are: By changing the composition and dosage ratio of the outer coating and the inner coating, the anti-oxidation and flame retardant effects of the titanium alloy are improved to a certain extent, and further adding the intermediate coating can significantly improve the anti-oxidation and flame retardant effects of the titanium alloy; In the inner coating, increase B 2 O 3 The proportion of K 2 O·SiO 2 Omit and appropriately increase TiO 2 The dosage is based on our daily experiments. 2 O·SiO 2 The protective effect in the coating combination is not very excellent; The role of the outer coating is to prevent pollution caused by chemical reactions with oxygen in the air. Therefore, the outer coating directly affects the anti-oxidation and flame retardant effects. The current 0.7% B 2 O 3, 46% Al 2 O 3 , 30% SiO 2 , 23.3% KOH outer coating composition, after long-term use, it is found that the wear resistance, corrosion resistance, high temperature oxidation resistance and other properties of the above coating need to be improved. Therefore, after repeated tests, titanium diboride (TiB 2 ), to improve the performance of the outer coating; The intermediate coating is: rare earth modified regranulated nanostructured Al 2 O 3 and TiO 2 , which works as follows: 1. Improve coating performance: Rare earth modification can improve Al 2 O 3 and TiO 2 The microhardness of the coating is increased, the friction coefficient is reduced, and the wear resistance is improved. This is because the addition of rare earth elements can change the microstructure of the coating, forming a bimodal microstructure, including a completely melted area and a partially melted area, thereby improving the performance of the coating.
[0016] 2. Antioxidant properties: Rare earth elements such as CeO 2 The addition of CeO can improve the antioxidant properties of the composite material. 2 Can stabilize ZrO 2 , thereby improving the material's resistance to high temperature oxidation. DETAILED DESCRIPTION
[0017] The present invention is further described below by specific examples and comparative examples. However, it should be understood that these examples and comparative examples are only used for more detailed and specific description and should not be construed as limiting the present invention in any form.
[0018] Example 1
[0019] An aviation titanium forging coating, characterized in that it is divided into two layers: an inner coating and an outer coating: Inner coating: TiO 2 45%, B 4 C 11%, B 2 O 3 34%, MgO 10%; Outer coating, B 2 O 3 0.7%, Al 2 O 3 46%, SiO 2 30%, KOH 23.3%; The treatment process is as follows: clean the aviation titanium forgings, dry them; weigh TiO 245%, B 4 C 11%, B 2 O 3 34%, MgO 10%; then mix the raw materials and ball mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water and stir until the viscosity reaches 50-80 centipoise to prepare the inner coating paint, and then brush the inner coating paint on the surface of the aviation titanium forging with a thickness of 0.3mm and dry it naturally; then weigh 0.7% B according to the mass percentage 2 O 3 , 46% Al 2 O 3 , 30% SiO 2 , 23.3% KOH, then mix and ball-mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the inner coating with a thickness of 0.3mm, and air-dry naturally to complete the treatment of aviation titanium forgings.
[0020] Example 2
[0021] An aviation titanium forging coating, characterized in that it is divided into two layers: an inner coating and an outer coating: Internal coating: TiO 2 42%, B 4 C 6%, K 2 O·SiO 2 24%, B 2 O 3 22%, MgO 6%; Outer coating, B 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%; The treatment process is as follows: clean the aviation titanium forgings, dry them; weigh TiO 2 42%, B 4 C 6%, K 2 O·SiO 2 24%, B 2 O 3 22%, MgO 6%; then mix the raw materials and ball mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water and stir until the viscosity reaches 50-80 centipoise to prepare an inner coating paint, and then brush the inner coating paint on the surface of the aviation titanium forging with a thickness of 0.3mm and air dry naturally; then weigh B according to mass percentage 2O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%, then mix, and ball mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the inner coating with a thickness of 0.3mm, and dry naturally to complete the aviation titanium forging.
[0022] Example 3
[0023] An aviation titanium forging coating, characterized in that it is divided into two layers: an inner coating and an outer coating: Inner coating: TiO 2 45%, B 4 C 11%, B 2 O 3 34%, MgO 10%; Outer coating, B 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%; The treatment process is as follows: clean the aviation titanium forgings, dry them; weigh TiO 2 45%, B 4 C 11%, B 2 O 3 34%, MgO 10%; then mix the raw materials and ball mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water and stir until the viscosity reaches 50-80 centipoise to prepare an inner coating paint, and then brush the inner coating paint on the surface of the aviation titanium forging with a thickness of 0.3mm and air dry naturally; then weigh B according to mass percentage 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%, then mix, and ball mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the inner coating with a thickness of 0.3mm, and dry naturally to complete the aviation titanium forging.
[0024] Example 4
[0025] An aviation titanium forging coating, characterized in that it is divided into three layers: an inner coating, an intermediate coating and an outer coating: Inner coating: TiO 2 45%, B 4 C 11%, B 2 O 3 34%, MgO 10%; Intermediate coating: rare earth modified regranulated nanostructured Al 2 O 3 and TiO 2 ; Outer coating, B 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 2 10%; The treatment process is as follows: clean the aviation titanium forgings, dry them; weigh TiO 2 45%, B 4 C 11%, B 2 O 3 34%, MgO 10%; then mix the raw materials and ball mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water and stir until the viscosity reaches 50-80 centipoise to prepare an inner coating paint, and then brush the inner coating paint on the surface of the aviation titanium forging with a thickness of 0.3mm and dry it naturally; weigh Al according to the mass ratio of 87:13:2:2 2 O 3 、TiO 2 、ZrO 2 and CeO 2 , ball milling on a ball mill to form a powdery mixture, spray drying the ball milled powder to form a plasma sprayed powder form, heat treatment and plasma treatment of the spray dried powder, the particle size of which is 20 to 50 microns, and finally plasma spraying of the aviation titanium forgings after the inner coating is brushed, the spraying thickness is 0.3mm, and it is naturally air-dried to form an intermediate coating; then, according to the mass percentage, B 2 O 3 0.7%,Al 2 O 3 36%, SiO 2 30%, KOH 23.3%, TiB 210%, then mix, and ball mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the intermediate coating with a thickness of 0.3mm, and dry naturally to complete the treatment of aviation titanium forgings.
[0026] Comparison Example Example 1 in the patent application number CN102675952B filed by the applicant in 2012: Cleaning TC4 titanium plate blank; weighing 42% TiO 2 , 6% of B 4 C, 24% of K 2 O·SiO 2 , 22% of B 2 O 3 , 6% MgO; then mix the raw materials and ball mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water and stir until the viscosity is appropriate (50-80 centipoise) to prepare the inner coating paint, and then brush the inner coating paint on the surface of the TC4 titanium plate blank with a thickness of 0.3mm and air dry naturally; then weigh 0.7% B according to the mass percentage 2 O 3 , 46% Al 2 O 3 , 30% SiO 2 , 23.3% KOH, then mix and ball-mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a suitable viscosity (50-80 centipoise), brush on the outer surface of the inner coating with a thickness of 0.3mm, and air-dry naturally to complete the treatment of the TC4 titanium plate.
[0027] Effect experiment 1: Antioxidant properties Experimental method: 6 pieces of titanium alloy with a size of 1 cm×1 cm and a thickness of 2 mm were prepared, 5 of which were treated according to the treatment processes of Examples 1-4 and the control group, and the other piece was not treated at all as the reference group. The temperature of 900°C was selected for the cyclic oxidation test, and the sample was placed in a high temperature furnace for 40 hours.
[0028] Determination method: Before and after oxidation, use a balance (electronic balance with an accuracy of 0.0001g) to measure the mass change of the sample and calculate the mass change ratio. The experimental results are shown in Table 1.
[0029] Table 1
[0030] From the above data we can see that: 1. Compared with the baseline group, the control group (Example 1 in CN102675952B) has shown excellent antioxidant performance, in which the mass change ratio is reduced from 0.518% to 0.251%.
[0031] 2. Compared with the control group, Example 1 mainly adjusts the components and proportions of the inner coating. First, the adjustment further reduces the oxidized mass proportion. However, since the inner coating is adjusted and the outer coating is not adjusted, its antioxidant performance does not show a significant decrease, but only decreases to 0.208%, that is, the current outer coating still has the defect of being oxidized.
[0032] 3. Compared with the control group, Example 2 mainly adjusts the components and proportions of the outer coating. It can be seen that the antioxidant performance of this adjustment has been further improved compared with Example 1, and the mass change is 0.166%, which fully demonstrates that the outer coating directly affects the antioxidant effect.
[0033] 4. Compared with the control group, in Example 3, the components and proportions were adjusted in both the inner coating and the outer coating. It can be seen that the above adjustments have significantly improved the antioxidant properties of the titanium alloy, and the mass change is only 0.121%. This also shows that the adjustment of the above components and dosages has achieved unexpected technical effects.
[0034] 5. Compared with Example 3, Example 4 further adds an intermediate coating on the basis of Example 3. It can be seen that its antioxidant performance is improved to a mass change of only 0.087% compared with Example 3. This shows that the rare earth modified regranulated nanostructured Al 2 O 3 and TiO 2 It can further improve the oxidation resistance of titanium alloy.
[0035] Effect experiment 2: Flame retardant performance test of flamethrower Sample preparation: Prepare 3 titanium forging substrates of the same size (1 cm × 1 cm, thickness 2 mm) and ensure that the surface is clean and free of oil stains.
[0036] The titanium forging substrate coating was prepared using the methods of the control example, example 3 and example 4 respectively.
[0037] Flame spray gun settings: The flame temperature of the flame spray gun is 1300 degrees Celsius; the flame spray gun is 30 cm away from the test sample, and the ignition time is set to 5 seconds.
[0038] The time for the above coating to be ignited is shown in Table 2 below: Table 2
[0039] For the above data, the ignition time of the control group is 9.2s, which is a relatively conventional coating ignition time in the industry. On the basis of the control group, the flame retardant time of Example 3 and Example 4 is further extended, that is, the products prepared by the present invention have very excellent flame retardant properties.
[0040] The above-described embodiments are exemplary and are not intended to limit the invention which is further described in the claims.
Claims
1. An aviation titanium forging coating, characterized in that: It includes an inner coating and an outer coating, wherein the inner coating is composed of the following raw materials in terms of mass percentage: Inner coating: TiO2 45%-50%, B4C 6%-11%, B2O3 28%-34%, MgO 6%-10%, the total mass percentage of the above raw materials is 100%; The outer coating layer is composed of the following raw materials in terms of mass percentage: Outer coating: B2O3 0.7%-2.0%, Al2O3 26%-36%, SiO2 30%-32%, KOH 23.3%-30%, TiB2 10-15%. The total mass percentage of the above raw materials is 100%.
2. The aviation titanium forging coating according to claim 1, characterized in that: Also included is an intermediate coating, which is rare earth modified regranulated nanostructured Al2O3 and TiO2.
3. The aviation titanium forging coating according to claim 2, characterized in that: ZrO2 and CeO2 are used as composite additives for synergistic modification, wherein the mass ratio of Al2O3, TiO2, ZrO2 and CeO2 is 87:13:2:
2.
4. The aviation titanium forging coating according to claim 1, characterized in that: The inner coating is composed of the following raw materials in terms of mass percentage: TiO245%, B4C 11%, B2O334%, MgO 10%; The outer coating layer is composed of the following raw materials in terms of mass percentage: B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB2 10%.
5. The aviation titanium forging coating according to claim 3, characterized in that: The inner coating is composed of the following raw materials in terms of mass percentage: TiO245%, B4C 11%, B2O334%, MgO 10%; The intermediate coating is rare earth modified regranulated nanostructured Al2O3 and TiO2, wherein ZrO2 and CeO2 are used as composite additives for synergistic modification, wherein the mass ratio of Al2O3, TiO2, ZrO2 and CeO2 is: 87:13:2:2; The outer coating layer is composed of the following raw materials in terms of mass percentage: B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB2 10%.
6. A treatment process for aviation titanium forging coating according to claim 4, characterized in that: The following steps are involved: The aviation titanium forging is cleaned and dried; TiO2 45%, B4C 11%, B2O3 34%, and MgO 10% are weighed according to mass percentage; the raw materials are then mixed and ball-milled on a ball mill to form a powdery mixture with a particle size of 350-450 meshes; varnish and banana water are then added and stirred to a viscosity of 50-80 centipoise to prepare an inner coating, and then the inner coating is brushed on the surface of the aviation titanium forging with a thickness of 0.3 mm and naturally air-dried; B2O3 0.7%, Al2O3 36%, SiO2 30%, KOH 23.3%, and TiB2 10% are then weighed according to mass percentage, and then mixed and ball-milled on a ball mill to form a powdery mixture with a particle size of 350-450 meshes; varnish and banana water are then added and stirred to a viscosity of 50-80 centipoise, and brushed on the outer surface of the inner coating with a thickness of 0.3 mm and naturally air-dried to complete the treatment of the aviation titanium forging.
7. A treatment process for aviation titanium forging coating according to claim 5, characterized in that: The following steps are involved: Clean the aviation titanium forgings and dry them; weigh TiO245%, B4C 11%, B2O334%, MgO according to mass percentage. 10%; then mix the raw materials, ball-mill them on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise to prepare an inner coating, and then brush the inner coating on the surface of the aviation titanium forging to a thickness of 0.3mm, and air dry naturally; weigh Al2O3, TiO2, ZrO2 and CeO2 according to a mass ratio of 87:13:2:2, ball-mill them on a ball mill to form a powdery mixture, spray-dry the ball-milled powder to form a plasma-sprayed powder form, heat-treat and plasma-treat the spray-dried powder respectively, and the particle size is 20-50 microns, and finally plasma spray the aviation titanium forging brushed with the inner coating, with a spray thickness of 0.3mm, and air dry naturally to form an intermediate coating; then weigh B2O30.7%, Al2O336%, SiO230%, KOH 23.3%, TiB2 10%, then mix, and ball mill on a ball mill to form a powdery mixture with a particle size of 350-450 mesh; then add varnish and banana water, stir to a viscosity of 50-80 centipoise, brush on the outer surface of the intermediate coating with a thickness of 0.3mm, and dry naturally to complete the treatment of aviation titanium forgings.
Citation Information
Patent Citations
Aviation TC4 titanium plate coating and method for treating titanium plate
CN102675952B
Monolithic nitrogen oxide selective reduction catalyst and preparation method thereof
CN102039205A
Aviation TC4 titanium plate coating and method for treating titanium plate
CN102675952A
Boride modified glass ceramic based composite high-temperature oxidation resisting coating and preparation method thereof
CN106587629A
Composite ceramic coating for insulating bearing of wind driven generator and preparation method of composite ceramic coating
CN113549859A
Cited By
Welding wire without copper plating and preparation method thereof
CN119870785A